Alberto2
Alberto2
10-03-2015
Mathematics
contestada
Substitute y = 2x + 1 y = 3x - 1
Respuesta :
crisforp
crisforp
10-03-2015
2x+ 1 = 3x - 1 ;
1 + 1 = 3x - 2x ;
2 = x ;
x = 2 ;
Then, y = 2x2 + 1 = 5 ;
Answer Link
VER TODAS LAS RESPUESTAS ( 16+ )
Otras preguntas
‼️‼️‼️PLS HELP I WILL MARK U BRAINLIEST‼️‼️‼️ Which translation can be used to prove that figures two and three are congruent? A) (x, y) —> (x, y - 4) B)
Please help me answer these questions
Find the center and radius of the circle with the equation: (x=5)2 +(4-2)3-25
How are the 18th and 21th Amendments to Constitution alike? and How are they different?
Please help/ Solve the following:- 1+4x/6=3.5
Does anyone have a pet? If so, send a pic! :) I will mark brainliest if you send a picture!! :)
(6) Arrange the decimals in increasing order..(a) 0.8, 0.25, 0.21 (b) 0.85, 3/4' 0.857
Mangalore, India 5. Which conclusion is best supported by the Climograph? A. This city is part of a tropical rain forest B. This city is subject to seasonal mon
A culture of bacteria has an initial population of 74000 bacteria and doubles every 3 hours. Using the formula P t = P 0 ⋅ 2 t d P t =P 0 ⋅2 d t
whats 5+5? please help quick quick quick